A case of COVID-19 infection in a kidney transplant recipient after receiving the single dose of COVID-19 vaccination. (May 2022) - Rahbar, Maryam; Sharifi, Yasaman; Kazem Aghamir, Seyed Mohammad
Abstract: Introduction and importance: As immunocompromised individuals, kidney transplant recipients (KTR) were more prone to severe and prolonged COVID-19 infection. Case presentation: A 52-year-old man with a history of two kidney transplants for polycystic kidney disease (PKD) was hospitalized due to COVID-19 illness after receiving the first dose of COVID-19 vaccination with Sputnik V. After being admitted to the hospital, the patient was given Remdesivir and oxygen therapy. Clinical discussion: We reported a COVID-19 infection after the first dose of Sputnik V vaccination in an immunocompromised patient who did not follow the protocols after vaccination. Regardless of vaccination, he had been infected, but the vaccination saved him from severe infection despite his comorbidity. Conclusion: To summarise, infection with COVID-19 should be considered after vaccinations, particularly the first dose, in immunocompromised patients such as KTR, and protocols for these patients should be strictly followed. It is worth mentioning that even a full dose of vaccination does not provide full protection from infection to anyone, including KTR. Highlights: It is reported that immunocompromised patients, mainly KTR patients, develop a low level of SARS-CoV-2 antibody after vaccination. Even a single dose of vaccination in patients with comorbidities could prevent severe COVID-19 infection and severe lung involvement according to our findings. Even after a full dose of vaccination, even in normal people without immunocompromised conditions, the protocols should be carefully followed since there is always a risk of getting infected.